Methodology for designing humanitarian supply chains: Distribution of COVID-19 vaccines in Mexico - Eva Selene Hernández Gress; Neil Hernández-Gress; Karen Sujo Contla (Administrative Sciences, 2021)
This paper presents a methodology for designing a humanitarian supply chain (HSC) for immunization in Mexico. The study analyzes the abilities of HSCs provided in the literature and those that are relevant for the HSC vaccination in Mexico. In addition, the stakeholders involved in HSC for immunization were studied. A sentiment analysis of more than 900 newspaper articles was conducted to determine society's perception of the government's strategy for vaccine distribution. Considering these aspects and a review of the state-of-the-art in the design of supply chains, a methodology for HSC is proposed. Some of the findings are that resilience and agility, the most important abilities in HSCs in Mexico, can be achieved through government support and strong collaboration between different stakeholders, which was found to be the weakest point of the strategy. The problems observed in the vaccination strategy in Mexico were as follows: (1) a single physical space per municipality was defined for the application of the vaccine, (2) there is a shortage of vaccines, and (3) as far as we know, no methodology has been applied to carry out immunization. This approach considers the design of HSCs in terms of capabilities and stakeholders, which, to the best of our knowledge, is a novel aspect of the literature. This methodology can be used for various scenarios of HSCs in Mexico.
Keywords: 350; immunization supply chains; strategy; vaccination